IMPLEMENTASI PENDEKATAN INKUIRI PADA PEMBELAJARAN IPA - yudianto yudianto (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2015)
Lack of science learning achievement at MIN 1 Metro possible because learning methods used have not put forward the activity of students in the learning process. Inquiry learning is one of the alternative efforts to improve student achievement in science subjects at MIN 1 Metro. Research done by quasi-experimental approach with two classes of objects that the experimental class and control class. The results showed that the implementation of inquiry learning have a significant influence on the average value of learning achievement in science class VI MIN 1 Metro, as indicated by the average value of student learning outcomes in inquiry learning is better than learning approaches expository.